HUBUNGAN BEBAN KERJA DAN PENERAPAN PATIEN SAFETY TERHADAP STRES KERJA PADA PERAWAT DI RSUD BALARAJA TAHUN 2022 - Rena Safira; Bayu Imanuddin (Yayasan Nusantara Hasana Berdikari, 2023)
Increased workload is indirectly related to patient safety. This points to the low number of nurses so that it can cause danger to patients to attract more attention. Patient safety (patient safety) can be interpreted as the basic principle of health services which views that safety is the right of every patient in receiving health services. Stress can lead to human error and accidents. Where “50.9% of Indonesian nurses are known to experience work stress, often feel dizzy, lack of rest due to too high a workload and inadequate income. The purpose of the study was to determine the relationship between workload and the application of patient safety to work stress on nurses at the Balaraja Hospital in 2022. The research method used in this study was cross sectional. The population in this study were inpatient nurses at the Balaraja Hospital totaling 117 respondents. The instrument used is a questionnaire sheet. This study used the Chi-Square Test, with p-value 0.000 <0.05. There is a relationship between workload and the application of patient safety to work stress on nurses at the Balaraja Hospital in 2022.